Tuesday

January 27, 2015

January 27, 2015

Posted by **erick** on Thursday, June 10, 2010 at 2:35pm.

- math -
**Reiny**, Thursday, June 10, 2010 at 4:18pmg(x) = (2/3)x + 4

or

y = (2/3)x + 4

inverse :

x = (2/3)y + 4

3x = 2y + 12

2y = 3x - 12

y = (3/2)x - 6

test:

g(6) = (2/3)(6) + 4

= 8

g^-1(8) = (3/2)(8) - 6

= 12-6 = 6

my answer is correct

**Answer this Question**

**Related Questions**

Advanced Algebra - What is the inverse of each of the functions defined by the ...

Algebra - what is the inverse of the linear parent function? How would you graph...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

Pre-Calc - Does y=1/x have an inverse? It is a one-to-one function, so it should...

Pre-caluclus - I do not know how to solve for y to get the inverse of this ...

Very easy math - my teacher told me that the inverse of addition was subtraction...

math - Determine the inverse of f(x)=(x^3)-2 Is the inverse the switch of ...

inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...

math - how do you find the equations inverse and the domain of the inverse f(x...

Calculus - F(x) = 1-x and g(x) = 1/x These functions have the property that f = ...